2022
DOI: 10.1002/chem.202200917
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Activation of Imines by Chalcogen Bond Donors in a Povarov [4+2] Cycloaddition Reaction

Abstract: Recently, chalcogen bonding has been investigated in more detail in organocatalysis and the scope of activated functionalities continues to increase. Herein, the activation of imines in a Povarov [4+2] cycloaddition reaction with bidentate cationic chalcogen bond donors is presented. Tellurium‐based Lewis acids show superior properties compared to selenium‐based catalysts and inactive sulfur‐based analogues. The catalytic activity of the chalcogen bonding donors increases with weaker binding anions. Triflate, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 76 publications
0
30
0
Order By: Relevance
“…On the one hand, elimination of anionic species and the electrophilic activation of a carbonyl group (or a relevant imino group) are two of the most abundant reaction steps in organic chemistry. 8,13,41,63 On the other hand, we studied these model reactions in our previous works 38,70 and thus the results obtained in this work can be compared with the data obtained previously for other noncovalent organocatalysts.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…On the one hand, elimination of anionic species and the electrophilic activation of a carbonyl group (or a relevant imino group) are two of the most abundant reaction steps in organic chemistry. 8,13,41,63 On the other hand, we studied these model reactions in our previous works 38,70 and thus the results obtained in this work can be compared with the data obtained previously for other noncovalent organocatalysts.…”
Section: Introductionmentioning
confidence: 87%
“…[52][53][54][55] Organocatalysts based on ChB donors have gained increasing attention over the last five years. [56][57][58][59][60][61][62][63][64] A series of publications give unambiguous evidence that the catalytic activity of ChB donating species shows a trend similar to that of XB donors, namely the catalytic activity gradually increases from S to Te, and it is higher for cationic species compared to uncharged chalcogen-containing compounds. Thus, it has been shown that telluronium salts E (Ch = Te IV ) exhibit a sig- nificantly higher Lewis acidity compared to tellurium(II) derivatives B and lighter chalcogen(IV)-derived species, 65,66 whereas selenonium salts E (Ch = Se IV ) are better catalysts than their sulfonium analogues E (Ch = S IV ).…”
Section: Introductionmentioning
confidence: 99%
“…1, C–D ) compared to the uncharged catalysts A and B . 10,17–24 Moreover, the catalytic activity of the XB and ChB species featuring the halogen( iii ) or chalcogen( iv ) atoms ( E and F , respectively) is remarkably higher than that of halogen( i )- and chalcogen( ii )-containing species C and D , correspondingly. Thus, cationic iodine( i )-based catalysts C (in particular, iodoazolium salts 9,25–33 ) effectively catalyze a wide range of organic reactions, whereas cationic iodine( iii ) derivatives (iodonium salts E , X = I) featuring two σ-holes at the iodine atom possess even a higher catalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…The use of cationic selenium-based Lewis acids was further extended by Wang and co-workers in the activation of carbonyl functionalities (Wang et al, 2019). As the development of chalcogen-bonding catalysts moved on, telluriumbased catalysts were introduced and applied in the activation of trans-�-nitrostyrene (Wonner et al, 2019a) and crotonophenone (Wonner et al, 2020) for Michael reactions, as well as in the activation of a carbon-chloride bond (Steinke et al, 2021) and of imines (Steinke et al, 2022). Lately, hypervalent tellurium-based chalcogen-bonding donors were introduced in organocatalysis (Weiss et al, 2021;Zhou & Gabbaı ¨, 2021).…”
Section: Introductionmentioning
confidence: 99%